SOCIALIZATION OF ANALGESIC EFFECTIVENESS OF REED ROOT ETHANOL EXTRACT (Imperata cylindrica L.) ON MALE WHITE MICE - Dewi Kartika (JURNAL PENGMAS KESTRA (JPK), 2022)
Pain is an unpleasant experience due to the presence of tissue damage. When a tissue is injured or damaged, it results in the release of materials that can stimulate pain receptors such as prostaglandins that will result in a pain response. Therapy using analgesic drugs can relieve pain. Empirically the roots of reeds are used as folk remedies for pain relief. Phytochemical screening results showed that reed roots contained flavonoids. Flavonoids contained in the roots of reeds can reduce pain by inhibiting the work of the enzyme cyclooxygenase. Tests that have been carried out on twenty male white rats induced using the infra red plantar test prove that there is a difference in the resistance of mice in resisting heat induction after being given the extract. Twenty male mice are divided into four groups. Three groups were given reed root ethanol extract at doses of 15, 30 and 60 mg/kg bb, one negative control group was given 0.5% CMC-Na and a positive control group was given mefenamic acid. The data obtained were processed using a one-way ANOVA and followed by a 95% level test. The conclusion can be that the higher the concentration the greater the analgesic power exerted, it is seen that the longer the response of mice in resisting the heat induction of the plantar test infra red.